Previsão do posicionamento de partículas de nanosílica numa blenda polimérica imiscível e comprovação via turbidimetria - Johansen, Luis Henrique Balista (2016)
The optical behavior of polymer systems with nanoparticles was studied in order to quickly assess the location of the nanoparticles in the immiscible polymer blend phases and interface using optical microscopy. The systems were designed taking into consideration microrheological and optical requirements. The morphology was a droplet-matrix phase, with particle size in the range of the visible light. Polystyrene and polycarbonate were chosen according to the parameters previously established, forming blends PS/PC with 95/5 %wt. Hydrophobic and hydrophilic silicas were chosen as nanoparticles, which were added to the blends in amounts of 0,5% and 1%. The melt blending procedure helped to set the nanoparticles at specific locations including within the dispersed phase, matrix phase and interphase. The morphology and the location of the nanoparticle were confirmed via transmission electron microscopy. The light scattering was measured via the normalized transmitted light intensity over temperature, overpassing the Tg of the two polymeric component. The PS/PC blends showed an increase in the light scattering, following a sigmoidal shape, in the temperature range of PS and PC Tg’s. The addition of the nanosilica forming PS/PC/Nanosilica systems greatly reduces the light scattering, particularly above the Tg of the PS phase. The use of hydrophilic nanosilica does not show any hysteresis upon comparing data from heating and cooling cycles. This type of silica stays mainly trapped within the PC particle, little interfering with the light scattering. On the other hand using hydrophobic nanosilica a clear hysteresis between heating and cooling portions is observed. The presence of the hydrophobic silica, located at the PS/PC interphase, interfere with the light scattering intensity at this interface, and can be used to identify its presence. The proposed procedure can be used to fast control the mixing process, thus improving the effective action of the nanoparticles in the final properties of the polymer systems.